On Photography as Circumnavigation of Anthropology - Sterzi, Eduardo (PORTO ARTE: Revista de Artes Visuais, 2019)
Abstract “I do take photographs, but I am not a photographer [...]”. “I [...] see photography as a way of escaping from anthropology, leaving anthropology, just as I saw in indigenous anthropology, which I chose as a profession, as a way of getting away from Brazil.” Relations between anthropology and photography—however constant—have never been straightforward in Eduardo Viveiros de Castro’s intellectual development. For a long time, indeed until quite recently, he clearly evinced discomfort or hesitancy when asked to discuss his photographic experiences—perhaps due to an inability to pinpoint photography’s role in his increasingly consolidated and recognized anthropological practice. However, it is this very persistence of his photography—despite his discomfort—that ought to be examined. Resumo “Eu fotografo, mas não sou fotógrafo [...]”. “Eu [...] vejo a fotografia como um modo de fugir da antropologia, de sair da antropologia, assim como vi na antropologia indígena que eu escolhi como profissão um modo de sair do Brasil.” Jamais foram simples – por mais que tenham sido constantes – as relações entre antropologia e fotografia no percurso intelectual de Eduardo Viveiros de Castro. Durante muito tempo, até recentemente, era perceptível certo desconforto do antropólogo quando convidado a discorrer sobre suas experiências fotográficas. Esse desconforto vinha talvez de não saber indicar exatamente qual o lugar que a fotografia ocupava em meio a uma prática antropológica sempre mais consolidada e reconhecida. É essa própria persistência da fotografia a despeito do desconforto que, porém, merece ser pensada.